Congenital megacolon associated with enterocolitis and hypoproteinemia - Karacadağ, Şükran; Sibinga, Maarten S. (The Turkish Journal of Pediatrics, 1972)
Of 30 patients with congenital megacolon, 5 developed enterocolitis. Serum protein levels were found to be low in 4 of these 5 patients and hypoproteinemia is emphasized as an additional sign in the enterocolitis of Hirschsprung’s disease.